(untitled) (Al-Academy, 2024)
It has mixed views on the concept or the role (Portrait) carving human faces across historical periods. The counting and historical document recording profiles for individual, promised impression represents promised impression represents the importance and greatness of personal without attention logs features and individual features, and in all cases the (portrait) was working for celebrated personality, glorifying and out of respect for his role heroic or reputation or social status.But if we intend carving human faces one varieties of art in sculpture became necessary for us to proceed from the statement which affirms "The requirement of art to be liberated from their recovery forms as they are in the outside world" and here we begin to wonder which is the problem of our research: Is (Portrait) art or documentary record of the character ? And if so , is it a true portrayal of the human form, or is it a piece of art embodies the artist’s creativity and his imagination of the form to be filmed? What are the differences between (Portrait), which is creation or art , and the craft one?These questions were motivated by my interest to search for the origin of the sort of the sculpture and trace its roots to learn how to embody the sculptor the people’s faces through the ages of civilization, and find out whether this type of sculpture belongs to art and creativity, or not ?